Stable lead(ii) boroxides. Issue 42 (26th April 2018) - Someşan, Adrian-Alexandru; Le Coz, Erwann; Roisnel, Thierry; Silvestru, Cristian; Sarazin, Yann
Abstract : The syntheses of the first lead(ii ) boroxides are reported. These stable, structurally characterised complexes do not decompose to oxoclusters. A melting temperature of 141 °C was determined for an organolead(ii ) boroxide. Abstract : The first examples of lead(ii ) boroxides, [Pb(OB{CH(SiMe3 )2 }2 )2 ] (1 ) and [{N^C}PbOB{CH(SiMe3 )2 }2 ] (5; N^C = 2-Me2 NCH2 C6 H4 ), were prepared via simple protocols. These structurally characterised compounds are stable and, unlike lead(ii ) alkoxides and siloxides, do not trigger uncontrolled formation of lead(ii ) oxoclusters.